Cost-effectiveness analysis of toripalimab plus chemotherapy versus chemotherapy alone for advanced non-small cell lung cancer in China - Zhang, Mengdie; Xu, Kai; Lin, Yingtao; Zhou, Chongchong; Bao, Yuwen; Zhang, Lingli; Li, Xin (Frontiers in Immunology, 2023)
Abstract Background Toripalimab is the first domestic anti-tumor programmed death 1 antibody marketed in China. The CHOICE-01 trial (identifier: NCT03856411) demonstrated that toripalimab plus chemotherapy can significantly improve the clinical outcomes of advanced non-small cell lung cancer (NSCLC) patients. However, whether it is cost-effective remains unknown. Given the high cost of combination therapy, a cost-effectiveness analysis of toripalimab plus chemotherapy (TC) versus chemotherapy alone (PC) for the first-line treatment of patients with advanced NSCLC is required. Methods A partitioned survival model was adopted to predict the course of disease in advanced NSCLC patients on TC or PC from the perspective of the Chinese healthcare system over a 10-year horizon. The survival data were obtained from the CHOICE-01 clinical trial. Cost and utility values were obtained from local hospitals and kinds of literature. Based on these parameters, the incremental cost-effectiveness ratio (ICER) of TC vs. PC was measured, and one-way sensitivity analyses, probabilistic sensitivity analyses (PSA), and scenario analyses were performed to assess the robustness of the model. Results In the base case, TC was associated with an incremental cost of 18510 and an incremental quality-adjusted life year (QALY) of 0.57 compared with PC, resulting in an ICER of 32237/QALY which was lower than the willingness to pay (WTP) threshold (37654/QALY), TC was cost-effective. The health utility value of progression-free survival, the price of toripalimab, and the cost of best supportive care were factors that significantly influenced the ICER, but no change in any of them could change the model result. TC showed a 90% probability of being a cost-effective option at a WTP threshold of 37,654/QALY. In the 20 and 30-year time horizons, the results remained unchanged and TC remained cost-effective when the second-line treatment was switched to docetaxel. Conclusions At a WTP threshold of 37,654 per QALY, TC was cost-effective compared to PC for patients with advanced NSCLC in China.